2019
DOI: 10.1111/cns.13120
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood test provides a practical method for glioma evaluation and prognosis prediction

Abstract: Summary Objective To investigate the relationship between tumor characteristics and the preoperative counts of immune cells in peripheral blood test in glioma patients. Methods We included 260 WHO grades II‐IV patients who had preoperative peripheral blood test result from Sanbo hospital as training set. The 66 patients from Tiantan hospital was obtained for validation. RNA sequencing data from CGGA and TCGA datasets were used to evaluate the features of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Clinically, the WHO stage system is commonly used for prognostic prediction in glioma patients. However, it has been suggested that prognostic prediction in glioma patients may be complicated, and the prognosis in patients with same WHO stage glioma can vary dramatically [6,7]. Therefore, uncovering novel prognostic factors remains important for improving the quality of care for glioma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the WHO stage system is commonly used for prognostic prediction in glioma patients. However, it has been suggested that prognostic prediction in glioma patients may be complicated, and the prognosis in patients with same WHO stage glioma can vary dramatically [6,7]. Therefore, uncovering novel prognostic factors remains important for improving the quality of care for glioma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant to this statement, empirically, remarkably fully 13 independent studies just between 2018 and 2020 reported the same findings-that a higher neutrophil to lymphocyte ratio-a relative or absolute neutrophilia-correlated with shorter survival in GB [66][67][68][69][70][71][72][73][74][75][76][77][78]. Few parameters in any cancer have been so oft confirmed.…”
Section: Dapsone Gb and Neutrophilsmentioning
confidence: 85%
“…Our finding is consistent with the results of other studies. 12,13 Some researchers found that with the increase of glioma grade, the infiltration of granulocytes increases, and the two are positively correlated. 12 Also, the infiltration of granulocytes and lymphocytes in local tumor inflammation was related to NLR, which represents systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Some researchers found that with the increase of glioma grade, the infiltration of granulocytes increases, and the two are positively correlated. 12 Also, the infiltration of granulocytes and lymphocytes in local tumor inflammation was related to NLR, which represents systemic inflammation. 13 Our study further confirmed the correlation between local inflammation and systemic inflammation in glioma.…”
Section: Discussionmentioning
confidence: 99%